Exercise physiology: Energy, nutrition, and human performance - McArdle , W. D.; Katch, F. I.; Katch, V. L. (Wolters Kluwer Health, 2010)
With a legacy spanning more than 40 years, Exercise Physiology: Nutrition, Energy, and Human Performance has helped nearly half a million students and exercise science practitioners build a solid foundation in the scientific principles underlying modern exercise physiology. This widely praised, trendsetting text presents a research-centric approach in a vibrant, engaging design to make complex topics accessible and deliver a comprehensive understanding of how nutrition, energy transfer, and exercise training affect human performance. The extensively updated 9th Edition reflects the latest advances in the field as well as a rich contextual perspective to ensure readiness for today`s clinical challenges.